Customer-Driven Service Standards of Citizen Charter in Badan Kepegawaian Daerah Kabupaten Sidoarjo - Lailul Mursyidah; Isnaini Rodiyah; Nur Maghfirah Aesthetika; Ikhsan Setiawan; Radita Andriana Madjid (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2021)
The purpose of this study is to determine and describe the Customer-Driven Service Standards of Citizen Charter in Badan Kepegawaian Daerah Kabupaten Sidoarjo. This research is a qualitative descriptive study located Badan Kepegawaian Daerah Kabupaten Sidoarjo. The technique of determining informants using purposive sampling. The informants in this study were the Head of Badan Kepegawaian Daerah Kabupaten Sidoarjo, Head of Planning and Reporting, Planning and Reporting Staff, Civil Servants in Kabupaten Sidoarjo Government. Data collection techniques through interviews, observation, and documentation. The technique of analyzing data uses an interactive model consisting of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that customer-driven service standards are indicated by the formulation of service standards in accordance with the vision and mission of Badan Kepegawaian Daerah Kabupaten Sidoarjo and informed through the official website of the Badan Kepegawaian Daerah Kabupaten Sidoarjo.